Biodiesel and biogas recovery from Spirulina platensis. (April 2017) - Sumprasit, Nattapon; Wagle, Nisha; Glanpracha, Naraporn; Annachhatre, Ajit P.
Abstract: The aim of this research was to optimize the energy recovery in the form of biodiesel and biogas from ubiquitous Spirulina platensis microalgae. Investigations were undertaken to select appropriate cell disruption technique, organic solvent for lipid recovery and catalyst for transesterification reaction for biodiesel production from Spirulina platensis . Based on energy considerations, osmotic shock was the most suitable cell disruption technique which recorded highest lipid recovery yield of 8.9% when chloroform/methanol (1:2 v/v ) was used as solvent. The extracted lipid from Spirulina platensis was esterified into Fatty Acid Methyl Esters (biodiesel) using sulfuric acid as the catalyst with conversion up to 79.5%. Under these conditions, biodiesel yield of 7.1 % (based on biomass weight) was obtained. Investigations also brought out that the lipid-extracted residue can be used as feedstock for biogas production with the average methane yield of about 290 ml/gVS. Highlights: Energy recovery from Spirulina platensis investigated at laboratory scale. Biodiesel yield depended upon type of cell disruption technique and catalyst used. Osmotic shock yielded the best lipid recovery with minimum of energy input. H2 SO4 -catalyzed transesterification yielded the best biodiesel conversion yield. Lipid-extracted algal residue can be used as feedstock for biogas production.